Polioencephalomalacia associated with excess dietary sulfur in feedlot cattle (FAVE Sección Ciencias Veterinarias, 2019)
Polioencephalomacia (PEM) refers to cerebrocortical necrosis. In bovine the most frequent causes of PEM are dietary fiber deficit, thiamine deficiency and excess of sulfur (S). The objective of this work is to report an outbreak of PEM in feedlot cattle consuming S excess. The affected farm usually provided a finishing diet composed of 45% corn destillers grains with solubles, but 25 days before of the problem the inclusion of this component was increased in the diet (up to 70%). The anamnesis, individual and population clinical examinations, one necropsy and the collection of drink water and balanced meal samples were carried out. Affected animals were treated with thiamine, with a favorable response. In the pathological examination of the brain, edema and hemorrhages were observed, with severe cortical necrosis. The bacteriological culture of encephalon was negative. The drinking water contained 1 g / l of sulphates and the food 0.48% of S, so that the total estimated consumption of S was 0.58%. Dietary S excess could have favored the occurrence of this PEM outbreak . To the best of our knowledge, this is the first etiological description of S dietary excess associated with PEM in Argentina.
Keywords: cattle; cerebrocortical necrosis; sulfur